1996
DOI: 10.1073/pnas.93.24.13659
|View full text |Cite
|
Sign up to set email alerts
|

Zinc folds the N-terminal domain of HIV-1 integrase, promotes multimerization, and enhances catalytic activity

Abstract: The N-terminal domain of HIV-1 integrase contains a pair of His and Cys residues (the HHCC motif) that are conserved among retroviral integrases. Although His and Cys residues are often involved in binding zinc, the HHCC motif does not correspond to any recognized class of zinc binding domain. We have investigated the binding of zinc to HIV-1 integrase protein and find that it binds zinc with a stoichiometry of one zinc per integrase monomer. Analysis of zinc binding to deletion derivatives of integrase locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
280
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(290 citation statements)
references
References 43 publications
10
280
0
Order By: Relevance
“…To determine whether the temperature dependence of the unfolded state dimensions is a general phenomenon, and to relate its characteristics to the amino acid composition of the chain, we extended the study to other proteins (Table 1 and SI Materials and Methods): two variants of the highly charged IDP ProTα, which allow us to probe the N-and C-terminal halves of the polypeptide (ProTαN and ProTαC, respectively), whose charge content is very different (8); the N-terminal domain of HIV integrase (8), an IDP in which the folded structure is formed upon binding of Zn 2+ (48); and a 34-aa fragment of CspTm, which is not folding competent (18) (CspM34). The average hydrophobicities of the sequences according to the Kyte-Doolittle score (49) are −2.44 for ProTαC, −1.5 for ProTαN, −0.6 for integrase and CspM34, and −0.25 for λ-repressor.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the temperature dependence of the unfolded state dimensions is a general phenomenon, and to relate its characteristics to the amino acid composition of the chain, we extended the study to other proteins (Table 1 and SI Materials and Methods): two variants of the highly charged IDP ProTα, which allow us to probe the N-and C-terminal halves of the polypeptide (ProTαN and ProTαC, respectively), whose charge content is very different (8); the N-terminal domain of HIV integrase (8), an IDP in which the folded structure is formed upon binding of Zn 2+ (48); and a 34-aa fragment of CspTm, which is not folding competent (18) (CspM34). The average hydrophobicities of the sequences according to the Kyte-Doolittle score (49) are −2.44 for ProTαC, −1.5 for ProTαN, −0.6 for integrase and CspM34, and −0.25 for λ-repressor.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were then passed through an immobilized pepsin column (prepared in-house) at 50 l min Ϫ1 (0.1% (v/v) TFA, 15°C), and the resulting peptides were trapped on a C 18 trap column (Hypersil Gold, Thermo Fisher). The bound peptides were then gradient-eluted (5-50% CH 3 CN (w/v) and 0.3% (w/v) formic acid) across a 1-mm ϫ 50-mm C 18 HPLC column (Hypersil Gold, Thermo Fisher) for 5 min at 4°C). The eluted peptides were then subjected to electrospray ionization directly coupled to a high resolution Orbitrap mass spectrometer (LTQ Orbitrap XL with electron transfer dissociation, Thermo Fisher).…”
Section: Methodsmentioning
confidence: 99%
“…16). The N-terminal domain (NTD, residues 1-46) contains the zinc-binding HHCC motif, which is essential for the correct folding of this domain and function of the full-length protein (17)(18)(19)(20)(21)(22). The catalytic core domain (CCD, residues 56 -202) contains the DDE active site, which coordinates catalytic Mg 2ϩ ions and mediates catalysis of both 3Ј-processing and strand transfer reactions (23)(24)(25)(26)(27).…”
Section: Hiv-1 Integrase (In)mentioning
confidence: 99%
“…We reported that the elimination system could be blocked by processing fertilized eggs with Zn 2+ or ATA [1], and the characteristics of the rEri15 protein coincides with this result. There is a report that although Zn 2+ is needed to stabilize the folded state of the integrase and for enzymatic activity [12], the Mn 2+ -dependent nicking activity of the avian sarcoma virus integrase catalytic domain is inhibited by Zn 2+ [11]. The possibility does exist that Zn 2+ blocking the elimination system of the egg could result from the fact that Eri15 was inhibited.…”
Section: Characterization Of Reri15 Proteinmentioning
confidence: 99%
“…Though integrase has exo-and endonuclease activity [9][10][11][12][13][14][15][16][17][18], in spite of the recombinant full-length Eri15 protein that developed in the E. coli lacking part of the integrase core domain and DNA binding domain, endonuclease activity was discovered which could digest mtDNA (Fig. 3A).…”
Section: Characterization Of Reri15 Proteinmentioning
confidence: 99%